2020
DOI: 10.3390/agronomy10101549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Application of Urea and Urea-Formaldehyde/Triazone on Soybean and Corn Crops

Abstract: The objective of the study was to evaluate the effect of foliar application of urea and urea-formaldehyde, triazone-based fertilizers on soybean and corn crops. Four experiments were carried out, two on soybeans, one on first season corn, and the other on second season corn. The experiments were conducted using a randomized block design, with 5 treatments studied: T1—control without application of foliar nitrogen (N); T2—foliar application of conventional urea solution and three treatments with Hexion foliar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For legume crops, foliar application could reduce the inhibition role of nitrogen to root nodule development and symbiotic nitrogen fixation ( Lin et al, 2018 ; Nishida et al, 2018 ). Thus, foliar application of nitrogen fertilizer has become more popular, and the physiological effects of foliar urea application on crop plants have been explored extensively in recent years ( Hassanein et al, 2019 ; Cassim et al, 2020 ; Lyu et al, 2021 ). In wheat, foliar urea application altered storage protein distribution of grain by promoting the expression of the majority of storage protein-encoding genes ( Rossmann et al, 2019 ), but the global transcriptional profile of soybean after foliar urea application has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For legume crops, foliar application could reduce the inhibition role of nitrogen to root nodule development and symbiotic nitrogen fixation ( Lin et al, 2018 ; Nishida et al, 2018 ). Thus, foliar application of nitrogen fertilizer has become more popular, and the physiological effects of foliar urea application on crop plants have been explored extensively in recent years ( Hassanein et al, 2019 ; Cassim et al, 2020 ; Lyu et al, 2021 ). In wheat, foliar urea application altered storage protein distribution of grain by promoting the expression of the majority of storage protein-encoding genes ( Rossmann et al, 2019 ), but the global transcriptional profile of soybean after foliar urea application has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Likely, Aulya et al [ 66 ] observed a significant increase in maize leaf area through the application of 10% organic extract. Cassim et al [ 67 ] studied that foliar application enriched N solution increased by 14.7% higher corn yield over the control. Similarly, Paramesh et al [ 68 ] obtained higher cob yield and biomass of wheat compared to 100% RD of soil application.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the presence of MDU in Ur-formaldehyde ( Figure 3 e) will provide an intermediate molecular weight and degree of polymerization, contributing to the slow release of N. This compound, combined with certain amounts of unreacted urea, results in an intelligent fertilizer for agricultural use within the cultivation time of the plants. For example, Cassim et al [ 55 ] observed no increase in yield in cultures with the application of Ur-formaldehyde with 70% slow-release compounds; but, with proportions of 55 and 60% of slow-release compounds, the yield increases were significant.…”
Section: Discussionmentioning
confidence: 99%